Ecofeminist Philosophy and Transitivity Selections in Kaine Agary’s Yellow-Yellow - Ojarikre, Anthony (Journal of Gender and Power, 2024)
The term ecocriticism is used to refer to literary criticism that examines the relationship between literature and environment. Ecofeminism can be regarded as an off-shoot o sub-theory of ecocriticism. The interest here is not just environmental justice but “gender justice” in relation to the environment. The paper therefore looks at environmental exploitation of women using Kaine Agary’s Yellow-Yellow. The theoretical framework for the study is Transitivity. Transitivity devices are identified; their frequencies and percentages are calculated; while the foregrounded ones are used for analysis. The results show a parallel pillaging, exploitation and degradation of the environment and the female gender.